FRI0508 Clinical Presentations, Outcomes of Juvenile Dermatomyositis Patients Admitted in the Pediatric Intensive Care Unit. (9th June 2015) - Besançon, A.; Gitiaux, C.; Brochard, K.; Dupic, L.; Quartier, P.; Bodemer, C.; Bader-Meunier, B.
Abstract : Background: Juvenile dermatomyositis (JDM) is a rare and heterogeneous pediatric-onset idiopathic inflammatory myopathy. It is a heterogeneous disease which may be complicated by life-threatening complications. Identifying causes, clinical and biological manifestations and outcomes of such complications may be helpful for their better early management Objectives: We aim to describe the causes of admission in paediatric intensive care unit (PICU), clinical and biological presentation and outcomes of JDM patients Methods: Retrospective study of JDM patients admitted in two french paediatric PICUs from 2005 to 2013 among a cohort of 116 JDM patients followed during the same period. Results: 11/116 JDM patients (9.5%) (8 girls and 3 boys, median age at diagnosis: 9.0±3.1 years) were admitted in ICUs because of digestive involvement (digestive perforation: 2 patients, digestive ulceration: 1 patient, severe ileus: 1 patient), cardiac involvement (severe bradycardia: 1 patient, cardiac arrest: 1 patient), respiratory failure resulting from hypoxemic pneumonia (1 patient), thrombotic microangiopathy (TMA) (2 patients), posterior reversible encephalopathy syndrome (PRES) related to cyclosporine use (1 patient), and anaphylactic shock after an infusion of Rituximab. At admission in ICU, patients presented with some manifestations which did not usually occur in typical JDM:) generalized edema (6/11 patients), hyponatremia (9/11 patients), hypoalbuminemia (9/11 patients) and thrombocytopenia (7/11 patients). Treatment consisted in corticosteroids (including pulses of methylprednisolone in 5 patients), intravenous immunoglobulin (7), plasmapheresis (7), infusions of rituximab (4) and cyclophosphamide (2). The mean duration of stay in PICU was 18.2 days. One patient died in ICU from pneumocystis carinii pneumonia. The remaining 10 patients are in complete or partial remission with a median duration of follow-up of 4, 8 years. Conclusions: Severe digestive vasculopathy, cardiac and pulmonary involvements, TMA and therapy-related adverse events were responsible for admissions in PICU in 9, 5% of JDM patients in our cohorts. This report suggests that generalized edema, thrombocytopenia revealing TMA, hyponatremia and hypoalbuminemia are associated with severe JDM, and that pulses of methylprednisolone might favour digestive perforation in patients with preexisting gastrointestinal vasculitis. Outcomes was favourable in all the patients presenting with non-infectious severe complications. Disclosure of Interest: None declared